Point-of-Care Ultrasound to Detect Dilated Coronary Sinus in Adults - Zouheir Bitar; Mohamad Abdelfatah; Ossama Maadarani; Muath Alanbaei; Rashed Al Hamdan (CINQUILL Medical Publishers Inc., 2022)
Detecting dilated coronary sinus when assessing patients in an acute emergency with point-of-care ultrasound (POCUS) is important for differential diagnosis, including the detection of persistent left superior vena cava (PLSVC) and right ventricular dysfunction. Cardiac POCUS with agitated saline injections through the left and right antecubital veins is a simple bedside test to make the diagnosis. We present a 42-year-old woman with first-time rapid atrial flutter in whom POCUS confirmed the presence of dilated coronary sinus and PLSVC.